Penerapan Metode Kanguru terhadap Berat Badan dan Respons Fisiologis Bayi BBLR - Hartati, Shanti; Natalia, Regina (Pustaka Galeri Mandiri, 2026)
Low Birth Weight (LBW) infants, defined as infants born weighing less than 2,500 grams, are at higher risk of physiological instability and growth problems. One non-pharmacological nursing intervention applied in the care of LBW infants is Kangaroo Mother Care (KMC). This study aimed to describe the implementation of KMC and its association with changes in body weight and physiological responses in LBW infants within the nursing care process. This study employed a descriptive case study design using a nursing care approach conducted in the Neonatal Intensive Care Unit (NICU). The subject of the study was one clinically stable LBW infant. Data collection was carried out through nursing assessment, observation, physical examination, and medical record review. Observed parameters included body weight, body temperature, respiratory rate, heart rate, and oxygen saturation before and after the implementation of KMC. The results showed an increase in body weight from 1,945 grams to 2,118 grams following the application of Kangaroo Mother Care. The infant’s physiological responses remained within normal ranges, as indicated by stable body temperature, regular respiratory rate, stable heart rate, and adequate oxygen saturation. The application of Kangaroo Mother Care in nursing care may support physiological stability and weight gain in low birth weight infants. This intervention can be considered a supportive nursing approach that emphasizes family involvement in the care of LBW infants.